Critical Analysis of Magnetohydrodynamic Jeffery-Hamel Flow Using Cu-Water Nanofluid - Alam, Md S; Khan, MAH; Alim, MA (GANIT: Journal of Bangladesh Mathematical Society, 2016)
The effects of nanoparticles and magnetic field on the nonlinear Jeffery-Hamel flow using Cuwater nanofluid are analysed in the present study. The basic dimensionless governing equations are solved using power series, which is then analysed by applying a semi-numerical analytical technique called Hermite- Padé approximation. The velocity profiles are presented in convergentdivergent channels for various values of nanoparticles solid volume fraction, Hartmann number, Reynolds number and channel angle. The dominating singularity behavior of the problem is analysed numerically and graphically for nanofluid. The critical relationships among the parameters are also performed qualitatively with the effect of Cu-nanoparticles. GANIT J. Bangladesh Math. Soc.Vol. 34 (2014) 111-126